Chemo- and enantioselective analysis of high hydrophilic organophosphate pesticides by liquid chromatography under different elution modes - Oka-Duarte, Leandro; Cass, Quezia Bezerra; de Oliveira, Anderson Rodrigo Moraes [UNESP] (Elsevier, 2024)
Acephate and malathion are prevalent chiral organophosphate insecticides, giving rise to more toxic chiral metabolites such as methamidophos and malaoxon, respectively. Enantioselective separation of chiral pesticides is crucial due to the differing pharmacological, environmental, and toxicological profiles of enantiomers. This study systematically evaluates an enantio‑ and chemoselective performance of eight polysaccharide-based chiral columns (Chiralcel OB-H, Chiralcel OD-H, Chiralcel OJ-R, Chiralpak AD-H, Chiralpak AS-H, Chiralpak IG-3, Chiralpak IK-3, and Lux-Amylose-2) and ten mobile phases across multimodal elution (normal-phase, polar organic, and reversed-phase conditions). Within the 80 combinations per analyte, the chiral screening highlights specific enantioselectivity trends concerning hydrophilic and hydrophobic compounds when utilizing amylose- or cellulose-based polymers under different conditions. Notably, a set of columns including IK-3, OJ-R, AS-H, and AD-H demonstrated superior coverage, achieving at least a 62 % success rate for enantioseparation. For the resolution between the pairs acephate/methamidophos and malathion/malaoxon, where no further optimizations were undertaken, the success rate for enantio‑ and chemoselectivity was 10 % and 30 %, respectively.
Keywords: Chiral pesticide; Enantioseparation; Multimodal screening; Organophosphate